TEN GOOD PRACTICES IN ENVIRONMENTAL CONSTITUTIONALISM: STRUCTURE, TEXT AND JUSTICIABILITY - May, James R.; Daly, Erin (Novos Estudos Jurídicos, 2017)
Environmental constitutionalism is a relatively recent phenomenon at the confluence of constitutional law, international law, human rights, and environmental law. It embodies the recognition that the environment is a proper subject for protection in constitutional texts and for vindication by constitutional courts worldwide. This chapter posits ten “good practices” – those attributes that make effective outcomes more likely, but not assured – in environmental constitutionalism for advancing positive environmental outcomes considering energy, and governance and sustainability. Good practices in environmental constitutionalism can serve as a useful construct for considering the relationship between sustainability, energy and governance. Accordingly, Section A examines the ten practices that are consequential for effectuating environmental constitutionalism and positive environmental outcomes. Section B then explains how the Robinson Township decision out of the Commonwealth of Pennsylvania in the United States provides a recent example just how good practices can have a positive impact on environmental outcomes in practice.